AI and GenAI as Tools in the Hands of Islamic Terrorist Organisations - Czornik, Katarzyna ca. 20./21. Jh. (Journal for the study of religions and ideologies, 2025)
The paper demonstrates that AI, and currently GenAI, enable Islamic terrorist (jihadist) organisations to feel increasingly confident in the world of modern information and communication technologies. AI and GenAI have become highly effective tools in the hands of jihadist organisations, and their ease of use, wide and nearly unlimited availability combined with weak safeguards make them what can be described as intensifiers and catalysts of jihadism. GenAI provides a space for an almost revolutionary transformation of jihadist operations in terms of speed, efficiency and scale, while also allowing them to wage an effective "hallucinatory war". The use of AI and GenAI by jihadist organisations focuses on three main areas: 1) personalised propaganda and disinformation; 2) interactive, selective recruitment and radicalisation; 3) combat applications and use on the battlefield (autonomous vehicles and drones). In this context, the religious and philosophical perspective is crucial. A challenging and problematic issue is AI’s alignment with societal values and Islamic teachings, and its potential use by jihadists.